PENINGKATAN PENGETAHUAN PETANI TENTANG DAMPAK PENGGUNAAN PUPUK KIMIA - N. Ai Erlinawati; Andhika Lungguh Perceka; Hasbi Taobah Ramdani; Gina Nafsa Mutmainna; Herlin Rusyani (Jurnal Pengabdian Masyarakat DEDIKASI, 2022)
Direct risk of exposure to pesticides can occur not only during the spraying process, but can also occur during the mixing process, even after the spraying process. Farmers' knowledge of using personal protective equipment (PPE) when spraying is a risk factor for poisoning. Situation analysis Intensive and unprocedural and ineffective use of pesticides. The use of pesticides that are not as recommended is caused by the knowledge factor of the farmers within themselves, namely perceptions and low knowledge of the use of pesticides according to recommendations that are still wrong or low. This activity is to provide education on the behavior of farmers spraying pesticides in applying the use of pesticides in the field (land). The solution offered by the implementing team is to provide understanding and education on how to use personal protective equipment, how to pay attention to wind direction and how to mix pesticides to farmer groups. The results obtained before the implementation of the provision of material and training were 22 people at the sufficient level and 18 people at the less level. After education, 30 people were in the good category and 10 people were in the enough category. Educational activities that have been carriedout by the implementing team can be a solution and a respondent for farmer groups as an effort to reduce the level of risk of exposure to pesticides